Classic Ehlers–Danlos Syndrome in a Son and Father with a Heart Transplant Performed in the Father - Sen, Paushpala; Butler, Merlin G. (Journal of Pediatric Genetics, 2019)
We report a 13-year-old male patient with severe orthopedic problems including features of a connective tissue disorder and a heterozygous c.305T > A variant found within exon 3 of the autosomal dominant collagen (COL5A1) gene causing the classic Ehlers–Danlos syndrome. This variant has not been reported previously and identified as having an unknown clinical significance but classified as trending damaging per in silico prediction with high conservation among species. Our patient's father had the same gene variant and similar features of stretchable skin, easy bruising, and multiple joint dislocations. The father had unexplained heart failure requiring cardiac transplantation at 43 years of age.
Keywords: classic Ehlers–Danlos syndrome with COL5A1 gene variant; joint hypermobility; poor skin healing and easy bruising; heart transplant